Orally administered Lactiplantibacillus plantarum OLL2712 decreased intestinal permeability, especially in the ileum: Ingested lactic acid bacteria alleviated obesity-induced inflammation by collaborating with gut microbiota - Wang, Yimei; Takano, Tomohiro; Zhou, Yingyu; Wang, Rong; Toshimitsu, Takayuki; Sashihara, Toshihiro; Tanokura, Masaru; Miyakawa, Takuya; Nakajima-Adachi, Haruyo; Hachimura, Satoshi (Frontiers in Immunology, 2023)
Chronic inflammation caused by dietary obesity has been considered to induce lifestyle-related diseases and functional ingredient with anti-inflammatory effects is attracting attention. In this study, we elucidated the mechanisms of Lactiplantibacillus plantarum (basonym: Lactobacillus plantarum) OLL2712 in suppressing obesity-induced inflammation using high fat diet (HFD)-fed mice obesity model. After 3-week administration of the heat-treated lactic acid bacteria (LAB), the gene expression levels of proinflammatory cytokines were downregulated in adipose tissue, colon, and Peyer’s patches (PP)-derived F4/80+ cells. The LAB treatment alleviated obesity-related gut microbiota imbalance. L. plantarum OLL2712 treatment helps maintain intestinal barrier function, especially in the ileum, possibly by preventing Occludin downregulation. Our results suggest that the oral administration of the LAB strain regulated the gut microbiota, suppressed intestinal inflammation, and improved the gut barrier, which could inhibit the products of obesity-induced gut dysbiosis from translocating into the bloodstream and the adipose tissue, through which the LAB finally alleviated the inflammation caused by dietary obesity. Barrier improvement was observed, especially in the ileum, suggesting collaborative modulation of the intestinal immune responses by ingested LAB and microbiota.